The Global South in a new scenario of great power competition and the international liberal order - Nieto Minaya, Willy Felix (2024)
The growing confrontation between China and the United States has led the latter to adopt divisive rhetoric that pits the current liberal international order, driven by Western powers, against an alleged alternative model being developed by China, which is often labeled as revisionist. Amidst this confrontation, the concept of the Global South has gained increasing relevance, particularly in relation to the expectation of its stance, whether in favor of or against the liberal international order. This article has a dual purpose: on one hand, to analyze the position of the Global South in this new scenario of great power competition; on the other hand, to elucidate its stance towards the so-called liberal international order. To achieve these objectives, the dynamics of the two competing powers will first be examined, followed by an analysis of the Global South’s dynamics based on its particular interests, strategic positions, and employed mechanisms.